Thin-film transistors based on p-type Cu2O thin films produced at room temperature - Fortunato, Elvira Maria Correia (2017)
This work was funded by the Portuguese Science Foundation (FCT-MCTES) through projects PTDC/CTM/73943/2006, PTDC/EEA-ELC/64975/2006, ERC 2008 Advanced Grant (INVISIBLE Contract No. 228144) and IT R&D program of MKE (Contract No. 2006-S079-03, Smart window with transparent electronic devices) from ETRI Korea. We thank K. Nomura for the Seebeck measurements and N. Franco for the XRD analysis.